Profile of Class VII Students' Abilities at SMPN 8 Pamekasan in Solving Mathematical Problems in The Form of Story Problems on Flat-Formed Material - Saleh, Hairus; Trisanti, Yuliana (INTERAKSI : Jurnal Kependidikan, 2022)
This research aims to describe the profile of students with high, medium and low mathematical abilities in solving word problems on flat shapes. This study used descriptive qualitative method. Supporting instruments include mathematical ability tests, problem solving tests and interview guides. The data obtained from this research are the results of students' mathematical ability tests and the results of mathematical problem solving tests in the form of story questions, both written tests and interviews. The results of this research are that students with high mathematical abilities in understanding problems, planning solutions, carrying out solutions and re-examining problem solving are included in the good category. Students with moderate abilities in understanding problems are quite good, in planning solutions they are quite good, in carrying out problem solving plans they are in the poor category and in re-examining solutions they are not good enough. Students with low mathematical abilities in understanding problems are in the fairly good category, in planning solutions are quite good, while in carrying out and re-examining problem solving they are in the not so good category.